HAGIA SOPHIA SYMBOL OF ISLAMIC CIVILIZATION IN TURKEY - Tasbih, Muhammad Irfan (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Hagia Sophia is a historical building in Turkey and has been a UNESCO World Heritage Site since 1934 and in 2020. The events of the Conquest of Constantinople in 1453 are in the spotlight of the world today, one of the triggers is Turkish president Recep Tayip Erdogan changing the policy of the status of the Hagia Sophia museum to a mosque. It received a tremendous response from the world community, especially from the West and Islam. The pros and cons arise because they consider the status of Hagia Sophia as a world heritage that should not change its status and must become a cultural heritage object. This research uses library research, which identifies data including books, journals, articles, and others. The results of the study explain that the status of Hagia Sophia in Istanbul belongs to Turkish state law, not international law, so the Turkish president has the right to change the status of Hagia Sophia to a mosque which used to be a museum during the secular regime. Mustafa Kemal Ataturk and other countries should not have protested the decision. According to research from the Istanbul Economic Research Institute in June, 46.9% of respondents agreed with the change of Hagia Sophia to a mosque, while 38.8% of respondents rejected and wanted Hagia Sophia to remain a museum.